Nanostructured Borate Halides for Optical Second Harmonic Generation at Surfaces. Issue 25 (23rd June 2020) - Tan, Deming; Kirbus, Benjamin; Eng, Lukas M.; Ruck, Michael
Abstract : Optical second harmonic generation (SHG) at surfaces and interfaces is an exciting new technique. In order to achieve high surface specificity and sensitivity of the SHG technique, smaller particles of SHG materials are highly desired. Borate halides are regarded as a great source of SHG materials because of their outstanding nonlinear optical properties. Phase‐pure nanostructured samples of three borate halides of the type A 2 B5 O9 X were synthesized at low temperature in task‐specific ionic liquids (IL). Optimized reactions of acetates A (OAc)2 ( A = Sr, Ba) and boric acid B(OH)3 with the mixed IL [P66614 ] X ( X = Cl, Br) and LiNTf2 led to nano‐rods of Sr2 B5 O9 Cl, nano‐needles of Sr2 B5 O9 Br, and nano‐sheets of Ba2 B5 O9 Cl. The reaction route presented here might trigger the synthesis of other borate compounds. Efficient second‐order nonlinear conversion by the nanostructured borate halides was confirmed using confocal SHG microscopy. Abstract : Optically active materials by "Green Chemistry": Task‐specific ionic liquids were used as solvents for synthesizing nanostructured functional materials, while conventional routes to those materials usually need temperatures higher than 700 °C. The ionothermal method we report here greatly reduces the energy consumption and simplifies the reaction setup. Moreover, the nanostructured powders open the way into new applications of SHG materials.